Rapid eye movement sleep cycle, clock time and sleep onset - McPartland, Richard J; Kupfer, David J (Electroencephalography and clinical neurophysiology, 1978)
The phase of the REM sleep rhythm was studied in 10 normal subjects each of whom was sleep studied for 4 consecutive nights. For analysis, each night of sleep was aligned according to clock time and each minute was scored as REM or non-REM. With these data, REM probability was found as a function of clock time. Fractional harmonic analysis indicates a 90 min periodicity. The REM probability curve shows peaks occurring at 1:30 a.m., 3:15 a.m., 4:30 a.m., 5:45 a.m. and 7:00 a.m. Statistical measures comparing the time of REM sleep across subjects suggests that subjects tend to have REM sleep at the same time of the night as each other. The influence of elapsed time after sleep onset on REM sleep is also reestablished. Results indicate that the time of REM sleep is determined by both clock time and time of sleep onset, suggesting two clocks, one sleep dependent and the other related to the basic rest activity cycle (BRAC), which are responsible for driving REM sleep. Furthermore, the similarity of REM times across subjects indicates the possible existence of an extra-personae REM driving force linked to clock time and possibly the BRAC. :a phase du rythme de sommeil avec mouvements oculaires rapides (REM) a étéétudiée chez 10 sujets normaux dont chacun a été enregistré pendant 4 nuits consécutives. Pour l'analyse, chaque nuit de sommeil a été alignée suivant le temps réel et chaque minute a été scorée comme sommeil avec et sans mouvements oculaires rapides. A partir de ces données, la probabilité du sommeil REM s'est révélée être fonction du temps réel. Une analyse harmonique fractionnée indique une périodicité de 90 min. La courbe de probabilité du sommeil REM montre des pics survenant à: 1 h 30, 3 h 15, 4 h 30, 5 h 45, et 7 h. Des mesures statistiques comparant le moment du sommeil REM d'un sujet à l'autre suggèrent que les sujets tendent à avoir du sommeil REM aux mêmes moments de la nuit. L'influence du temps écoulé après l'endormissement sur le sommeil avec mouvements oculaires rapides est également réétablie. Les résultats indiquent que les moments de sommeil REM sont déterminés à la fois par le temps réel et le temps horloges, l'une dépendent dy somemeil et deux horloges, l'une dépendant du sommeil et l'autre liée au BRAC, sont responsables de la survenue du sommeil REM. En outre, la similarité des temps de REM entre sujets indique l'existence possible d'un facteur extrapersoneel lié au temps réel et possiblement au BRAC.